Anestezjologia i intensywna terapia The relationship between ”aspirin resistance” and post-operative cardiac ischaemic events in coronary artery bypass grafting patients - Golański, Ryszard; Watała, Cezary; Iwaszkiewicz-Zasłonka, Alicja; Kuliczkowski, Wiktor; Zasłonka, Janusz; Golański, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: The lack of adequate platelet activation blocking by acetylsalicylic acid (ASA) in patients after coronary artery bypass grafting (CABG) in extracorporeal circulation may be one explanation of post-operative cardiac ischaemic events (PCIE) due to early vascular graft closure. Aim: The aim of the study was to assess the frequency of post-operative cardiac ischaemic events (PCIE) in patients with the laboratory aspirin resistance (LAR) phenomenon present. Materials and methods: The study included 46 patients (all men, age 59.6±7.8 years) operated on with the CABG procedure. Patients received 325 mg of ASA starting on the first day after the operation. Platelet reactivity was assessed on the 10th day after the operation using whole blood aggregation, PFA-100TM closure time and thromboxane B 2 plasma concentration. The results obtained allowed patients to be classified into 5 categories: A – resistance (4 criteria present), B – weak blockade (3 criteria present), C – medium blockade (2 criteria present), D – blockade (1 criterion present), E – complete blockade (no criteria present). PCIE were diagnosed on the basis of ECG analysis and enzymatic results. Results: There were 12 patients with PCIE, in 3 of whom myocardial infarction was diagnosed. According to LAR criteria there were 5 patients included in group A (3 of them (60%) had PCIE), 5 in group B (2 of them (40%) had PCIE), 15 in group C (2 of them (13%) had PCIE), 17 in group D (5 of them (29%) had PCIE) and 4 in group E (no patient with PCIE). The most significant difference between patients with and without PCIE was observed for dTxB 2 concentrations. Conclusions: 1. Post-operative cardiac ischaemic events are more frequent in patients with the laboratory aspirin resistance phenomenon. 2. The most distinctive laboratory measure of this phenomenon and ischaemic events is the dynamic generation of TxB 2 .